Identification of tumor antigens and T-cell epitopes, and its clinical application - Paschen, Annette; Eichmüller, Stefan B.; Schadendorf, Dirk (Cancer immunology immunotherapy, 2004)
The capability of antigen-specific CD8+ and CD4+ T lymphocytes to mediate antitumor immunity has generated remarkable interest in the identification of target antigens and their epitopes. The classical strategy to define tumor antigens is based on the employment of in vivo sensitized tumor-reactive T lymphocytes from cancer patients. These lymphocytes are used to screen an autologous tumor cDNA expression library for the target antigen. Alternatively, antibodies from the serum of cancer patients can be applied to screen a tumor-derived phage expression library for immunogenic cellular structures. In addition, potential target antigens have been selected by gene expression profiling searching for overexpressed gene products in neoplastic cells compared with normal tissues. B-cell target structures and overexpressed gene products have to be verified as T-cell antigens by the strategy of “reverse immunology.” Therefore, T cells are sensitized in vitro by autologous dendritic cells loaded with predicted antigenic peptide ligands for a given HLA allele or with the global antigen. These different approaches led to the identification of a still growing number of antigenic peptides providing the basis for the development of new active and passive immunotherapies and for the monitoring of spontaneous and vaccine-induced T-cell responses. Some of these antigens and/or their epitopes are now validated in different clinical regimens for their capability to mediate potent T-cell immunity in cancer patients.